Syntheses of Spiro(2-oxopyrrolidinyl)-5,4′-pyrazolones via Organocatalyzed Michael/Ammonolysis Cascade Reaction of 4-Aminopyrazolones and α,β-Unsaturated Acyl Phosphates - Li, You-Fen; Chen, Zheng-Jun; Jiao, Wen-Ya; Chen, Zhi-Jiao; Chen, Lin (Synlett, 2021)
The efficient organocatalyzed Michael/ammonolysis cascade reaction of N-protected 4-aminopyrazolones and α,β-unsaturated acyl phosphates has been developed. This tactic gives rise to architecturally multifarious spiro(2-oxopyrrolidinyl)-5,4′-pyrazolones in good productiveness (up to 88% yield) and with moderate to good diastereoselectivities (up to 20:1 dr). These novel hybrid heterocycles would be promising candidates for drug-discovery programs and chemical biology.
Keywords: spiro(2-oxopyrrolidinyl)-5,4′-pyrazolones; N-protected 4-aminopyrazolones; α,β-unsaturated acyl phosphates; organocatalysis; drug discovery; pharmacophores; medicinal chemistry; Michael/ammonolysis cascade reaction